2012
DOI: 10.1002/cmdc.201200403
|View full text |Cite
|
Sign up to set email alerts
|

N‐Cyano Sulfoximines: COX Inhibition, Anticancer Activity, Cellular Toxicity, and Mutagenicity

Abstract: From insects to cancer: N-Cyano sulfoximines were evaluated for COX inhibition and antiproliferative activity against a panel of cancer cell lines. The most active compound exhibited potent COX-2 inhibition, some selectivity for COX-2 over COX-1, only slight cytotoxicity towards healthy cells (HaCaT skin cells), and no mutagenic potential (as determined by an Ames assay).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
49
0
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 22 publications
0
49
0
1
Order By: Relevance
“…[20] Recently, we prepared a series of bioactive sulfoximines and demonstrated their potential applications in medicinal chemistry. [23] It was shown that the biological response significantly depended on the absolute configuration of the stereogenic sulfur atom. [23c] For obtaining those results, racemic compounds were prepared, which subsequently had to be resolved by HPLC using a chiral stationary phase.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[20] Recently, we prepared a series of bioactive sulfoximines and demonstrated their potential applications in medicinal chemistry. [23] It was shown that the biological response significantly depended on the absolute configuration of the stereogenic sulfur atom. [23c] For obtaining those results, racemic compounds were prepared, which subsequently had to be resolved by HPLC using a chiral stationary phase.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the optical rotations of 2 n and 4 n with the respective reported values proved that the oxidation had proceeded with retention of configuration. [23] It was shown that the biological response significantly depended on the absolute configuration of the stereogenic sulfur atom. was 93:7.…”
mentioning
confidence: 99%
“…Angeregt durch die Entdeckung des N-Cyansulfoximins Sulfoxaflor (14) als neuen Wirkstoffs für den Pflanzenschutz wurde ebenfalls die Bioaktivität des N-Cyansulfoximins 47 untersucht, wobei sich signifikante, selektive, COX-2-inhibitorische Eigenschaften herausstellten. [51] Dies lçste die Synthese einer Reihe von N-Cyansulfoximinanaloga anderer bekannter Sulfon-COX-2-Inhibitoren aus. Die Enantiomere von N-Cyansulfoximin 49, einem Analogon von DuP697 (48; DuPont Merck), wiesen auffällige Unterschiede auf: Ein Enantiomer von 49 stellte sich als potenter und selektiver COX-2-Inhibitor heraus, während das andere Enantiomer eine relativ schwache COX-1-und COX-2-Inhibition zeigte.…”
Section: Cox-2-inhibitorenunclassified
“…[7] Furthermore, the research group of Bolm has reported several bioactive sulfoximines with potent COX inhibitory activity, antiproliferative activity, cellular toxicity, and mutagenicity. [8][9][10] However, isosteric replacement in which the sulfur-bonded oxygen atom of sulfonamides (9) and acyl sulfonamides (4) is replaced by a nitrogen atom, that is, to respectively yield sulfonimidamides (12) and acyl sulfonimidamides (14), have been only sparsely applied in the area of drug design. For example, in the last decade, the research groups of Dodd and Malarcia have used sulfonimidamide-containing substances in organic synthesis, [11][12][13][14][15][16] and a few reports, including patent applications, have indicated the utility of the sulfonimidamide functional group in bioactive molecules.…”
mentioning
confidence: 99%